Carrying Capacity Analysis of Sustainable Groundwater Sources (Case Study in Sumberjati Village, Sillo District, Jember Regency) - Agus Luthfi; Moch. Fitroh Kardiansyah (Sekolah Pascasarjana Universitas Brawijaya, 2018)
Sumberjati Village is one of water supply area in East Jember Regency. The existence of natural resources potential, which is groundwater sources, give an impact to the excessive use of that common goods by local and nearby village. If this condition continues, in the long term, there will be water scarcity in Sumberjati Village. Therefore, the aim of this study is to analyse the carrying capacity of sustainable groundwater resources in Sumberjati Village. This research is using Principal Component Analysis (PCA) as main methods, which consist of 3 (three) components: (i) soil water resources (ii) environment; and (iii) social economy. Based on PCA analysis results, it is known that that for the groundwater resources component, variables that have a positive effect on the carrying capacity of groundwater resources in Sumberjati Village are; (i) number of water sources, and (ii) water wasted amount. While for the environmental component, the variables that have a positive effect is; (i) water quality, (ii) land conservation, (iii) erosion prevention, (iv) water pollution prevention, and (v) water distribution. For the Socio-Economic component, the variables that have a positive effect on the carrying capacity of groundwater resources are; (i) the ability to pay for water, and (ii) the number of households who can access the water